Business cycle in residential construction in Poland 2007–2022 - Marek Bryx; Janusz Sobieraj (Archives of Civil Engineering)
This article explores the dynamic interplay between the business cycle and the housing market in Poland from 2007 to 2022. It examines the complex relationship between economic cycles and the residential property sector, focusing on the impact of government intervention and market fluctuations. The research shows that the housing market is highly sensitive to external factors. It highlights the central role of the National Bank of Poland (NBP) in shaping the housing market through changes in interest rates and credit availability. The COVID-19 pandemic temporarily disrupted developer activity and housing demand, highlighting the vulnerability of the market to unexpected shocks. In addition to observations, this study calls for a critical analysis of housing policies, identifying potential shortcomings and offering recommendations for improvement. It underlines that economic crises are an inherent part of housing market cycles, promoting market cleansing and healthy competition. Finally, this research emphasises that the housing market is intertwined with broader economic trends. It highlights the need for central banks to strike a balance between managing inflation and supporting economic growth. This study contributes to a deeper understanding of the relationship between the housing market and the business cycle, providing valuable insights for policymaking and investment decisions.